Editorial policies on local authorship in rural health - Leonardo Vieira Targa; Mayara Floss (Revista Brasileira de Medicina de Família e Comunidade, 2020)
Introduction: Community engagement in health research potentially benefits researchers, institutions and local people. Objective: This work reviews health journal policies looking for local authorship instructions, and clear specific recommendations on ethic issues for rural, remote or communities from low and middle income countries research publications. Methods: A research at National Library of Medicine, CAPES and Embase identified 37 journals related to rural health. A review of all instructions to authors were conducted independently by two authors, looking for any mention of local co-authorship or how to relate to local communities in the publication guidelines of the included journals. Results: Eleven [n=11] journals fit the inclusion criteria and just one [n=1] had any instruction or ethic concern about local authorship on the author’s instructions. Most journals are from high income countries. Although the care in rural areas are more concentrated in Primary Care the journals were varied in its scope. Only four journals include in its description and scope primary care, general practice or family medicine. Conclusions: Authorship and publication policies should include specific and clear ethical recommendations related to community engagement in all major scientific communication vehicles. This should stimulate local participation through clear guidance to authors as a way of promoting a more inclusive, active and horizontal relationship between researchers and communities.